2019
DOI: 10.7454/epidkes.v2i2.3141
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Antenatal Care with Childbirth Complication in Indonesian’s Mothers (Data Analysis of The Indonesia Demographic and Health Survey 2012)

Abstract: Labor complications often lead to maternal death. A good antenatal care can reduce maternal and infant mortality. The purpose of this study was to analyze the relationship between antenatal care and labor complication among Indonesian’s mothers. Data of the Indonesia Demographic and Health Survey (IDHS) 2012 from 33 Provinces were used in this study. Samples consisted of 11.803 women aged 15-49 years who delivered baby at sometimes during the last 5 years before survey. A cross-sectional design was used.  Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
8
1
1
Order By: Relevance
“…It is possible that mothers still carried out antenatal visits despite their poor knowledge regarding COVID-19 transmission and worry about their pregnancy as they were more likely concerned about their pregnancy and resulting in no obstetric complication significant difference. These findings are in contrast to the previous study conducted by Bantas, Aryastuti, & Gayatri (2019). They found that antenatal visits were associated with the incidence of childbirth complications.…”
Section: Obstetric Complicationcontrasting
confidence: 99%
“…It is possible that mothers still carried out antenatal visits despite their poor knowledge regarding COVID-19 transmission and worry about their pregnancy as they were more likely concerned about their pregnancy and resulting in no obstetric complication significant difference. These findings are in contrast to the previous study conducted by Bantas, Aryastuti, & Gayatri (2019). They found that antenatal visits were associated with the incidence of childbirth complications.…”
Section: Obstetric Complicationcontrasting
confidence: 99%
“…3 Previous studies in Indonesia have examined several risk factors for maternal complications, including nullipara, younger and older age, low socioeconomic status, urban residence, and poor-quality antenatal visits. [4][5][6] As home to over 260 million people who are broadly dispersed across 34 provinces, Indonesia faces disparities in healthcare utilization. The utilization of healthcare services is mainly related to the accessibility of services.…”
Section: Introductionmentioning
confidence: 99%
“…Bantas, Aryastuti and Gayatri 2019 conducted a study on the relationship between antenatal care and childbirth complications. The results of the study stated that 92.6% of cases of labour complications were found in mothers with a history of ANC examinations not being carried out according to standards (Bantas et al, 2019). The optimal number of ANC visits will be able to prevent the occurrence of maternal emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the number of ANC visits of respondents who made ANC visits 6 times during their pregnancy was 73.1%. The results of research conducted by Bantas, Aryastuti, and Gayatri in 2019 stated that 79.3% of respondents conducted ANC visits according to standards (Bantas et al, 2019). Antenatal check-up visits at 4-week intervals until 28 weeks gestation, then every 2 weeks until 36 weeks gestation, and every week thereafter.…”
Section: Discussionmentioning
confidence: 99%